Interview by Adide to the director of the Institute of Evaluation, Enrique Roca - Equipo Editorial (ADIDE Federación, 2008)
The Act of Education establishes the Institute for Evaluation as a substitute of the former INECSE, and entrust to it -in cooperation with the Educational Authorities- the general assessment of the Educational System and the participation of Spain in international educational assessment as well as the development of National Standards of Educational Quality Indicators . In charge of these important duties is Mr Enrique Roca, who kindly let Avances en Supervisión Educativa interview him for this issue.